2020
DOI: 10.1111/hdi.12835
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal digital brachial index prior to hemodialysis access construction and cardiovascular mortality

Abstract: Introduction An abnormal ankle‐brachial index indicating presence of peripheral arterial disease (PAD) is known to predict mortality in end‐stage renal disease (ESRD). Hand ischemia, reflected by low finger pressures, is also a factor associated with increased mortality in patients undergoing hemodialysis (HD). The Aim of the present study is to determine whether an abnormal digital brachial index in ESRD patients prior to HD access surgery is related to lower survival rates. Methods A digital brachial index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…1,21,22 Several studies found that hand ischemia as reflected by a low systolic finger pressure (P dig ) was associated with increased mortality rates in HD populations. [6][7][8][9][10] Based on these findings, we hypothesized an association between drop in P dig (∂P dig ) during a MAT and mortality in CKD patients who were scheduled for access surgery. Interestingly, 52% of the individuals demonstrating a ∂P dig > 50 mmHg at the preoperative MAT had died after 4 years compared to just 15% with a ∂P dig < 15 mmHg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,21,22 Several studies found that hand ischemia as reflected by a low systolic finger pressure (P dig ) was associated with increased mortality rates in HD populations. [6][7][8][9][10] Based on these findings, we hypothesized an association between drop in P dig (∂P dig ) during a MAT and mortality in CKD patients who were scheduled for access surgery. Interestingly, 52% of the individuals demonstrating a ∂P dig > 50 mmHg at the preoperative MAT had died after 4 years compared to just 15% with a ∂P dig < 15 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may reflect lack of compensatory capacity of the vascular system in some of these fragile patients. [6][7][8][9][10] Prior to choosing the optimal type of HD access in an CKD patient, stratification of risk factors is required. For instance, a patient having multiple risk factors and possibly a limited life expectancy may benefit from a permanent indwelling line rather than from an arteriovenous fistula or loop.…”
Section: Introductionmentioning
confidence: 99%